2009
DOI: 10.1016/j.brat.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice implementation and staff emotional exhaustion in children's services

Abstract: Understanding the implementation of evidence-based practice (EBP) in community service settings is critical for the successful translation of research to practice. However, we have limited research evidence about the impact of EBP implementation on the mental health and social service workforce.In a previous study we demonstrated reduced staff turnover where an EBP was implemented with fidelity monitoring in the form of supportive ongoing supervision and consultation. Other research has shown that staff burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
79
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 38 publications
12
79
2
Order By: Relevance
“…Prior intervention research has even noted lower levels of stress in organizations that have successfully implemented a new EBP with a fidelity monitoring protocol, compared to treatment as usual programs with a new fidelity monitoring protocol (Aarons, Fettes, Flores, & Sornmerfeld, 2009). In the current study, we found that individual-level reports of morale had small to moderate significant positive correlations with three out of our four dependent variables, and that these associations were no longer significant after accounting for multiple constructs in a multivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…Prior intervention research has even noted lower levels of stress in organizations that have successfully implemented a new EBP with a fidelity monitoring protocol, compared to treatment as usual programs with a new fidelity monitoring protocol (Aarons, Fettes, Flores, & Sornmerfeld, 2009). In the current study, we found that individual-level reports of morale had small to moderate significant positive correlations with three out of our four dependent variables, and that these associations were no longer significant after accounting for multiple constructs in a multivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional exhaustion, or feelings of being emotionally overextended and exhausted by one’s work, is a component of workplace burnout (Maslach & Jackson, 1981) linked to turnover intentions and poor job performance (Cropanzano, Rupp, & Byrne, 2003). Encouragingly, child welfare providers who received training and consultation in an EBP had lower rates of emotional exhaustion compared to providers who provided services as usual (Aarons, Fettes, Flores, & Sommerfield, 2009). Aarons and colleagues (2009) attributed these findings to the structure provided by the EBP protocol and the instrumental and emotional support received from consultants on the job.…”
Section: Therapist Characteristics As Predictors and Moderators Of Atmentioning
confidence: 99%
“…Encouragingly, child welfare providers who received training and consultation in an EBP had lower rates of emotional exhaustion compared to providers who provided services as usual (Aarons, Fettes, Flores, & Sommerfield, 2009). Aarons and colleagues (2009) attributed these findings to the structure provided by the EBP protocol and the instrumental and emotional support received from consultants on the job. However, these hypotheses were not empirically tested.…”
Section: Therapist Characteristics As Predictors and Moderators Of Atmentioning
confidence: 99%
“…In addition to yielding superior client outcomes relative to alternative treatments, the uptake of EBPs has been associated with better workforce outcomes, such as reduced burnout, among community providers (Aarons, Fettes, Flores Jr., & Sommerfeld, 2009). A Delphi poll of psychotherapy experts in 2000 predicted that evidence-based psychotherapies would become mandated and, by extension, widely implemented by 2010 (Norcross, Hedges, & Prochaska, 2002).…”
mentioning
confidence: 99%